3(f+19)=-3

Simple and best practice solution for 3(f+19)=-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(f+19)=-3 equation:



3(f+19)=-3
We move all terms to the left:
3(f+19)-(-3)=0
We add all the numbers together, and all the variables
3(f+19)+3=0
We multiply parentheses
3f+57+3=0
We add all the numbers together, and all the variables
3f+60=0
We move all terms containing f to the left, all other terms to the right
3f=-60
f=-60/3
f=-20

See similar equations:

| 2x2+10=172 | | 4(4x-1)=2(2x+2)+4x | | 5+4n=1-7n | | 13.7+x=-9 | | 9/2x-18=1/2x+14 | | 4.x²=18 | | 40/65=x104 | | | | (x+8)^2=144 | | (x+8)62=144 | | (x+8)2=144 | | 23x(x12)=46x-21 | | d=43 | | 23x12=46x-21 | | 4x+500=125 | | x÷5/3=9/20 | | -38+2n=6(n-5) | | 3(5b+8)=-8b | | 3m-25m=63 | | (2-n)-5=30 | | (x-9)/8+5=7 | | x2−7x−60=0 | | {x-9}{8}+5=7 | | x-9/8+5=7 | | 77x-231=2079 | | 897=c+138 | | 7x-4-6=0 | | a+(-5)=8/3 | | 3x+6x–7=10 | | 2+3(3-8x)=-157 | | -31=-39y/8 | | 3•x+6=14 |

Equations solver categories